Association of N-acetyltransferase 1 Polymorphism and Bladder Cancer Risk: An Updated Meta-analysis and Trial Sequential Analysis. Issue 3 (July 2017) - Xu, Zicheng; Li, Xiao; Qin, Zhiqiang; Xue, Jianxin; Wang, Jingyuan; Liu, Zhentao; Cai, Hongzhou; Yu, Bin; Xu, Ting; Zou, Qin
Background: Individual studies of the association between N-acetyltransferase 1 (NAT1)*10 allele and bladder cancer susceptibility have shown inconclusive results. To derive a more precise estimation of any such relationship, we performed this systemic review and updated meta-analysis based on 17 publications. Methods: A total of 17 studies were investigated with 4, 322 bladder cancer cases and 4, 944 controls. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of the association. Subgroup analyses were conducted based on ethnicity, sex, source of controls and detecting methods. Then trial sequential analysis was performed to evaluate whether the evidence of the results was sufficient and reduce the risk of type I error. Results: There was no association between NAT1*10 allele and bladder cancer risk in a random-effects model (OR = 0.96, 95% CI, 0.84-1.10) or in a fixed-effects model (OR = 0.95, 95% CI, 0.87-1.03). In addition, no significantly increased risk of bladder cancer was found in any other subgroup analysis. Then, trial sequential analyses demonstrated that the results of our study need to be further verified. Conclusions: Despite its limitations, the results of the present meta-analysis suggested that there was no association between NAT1* 10 allele and bladder cancer risk. More importantly, our findings need to be further validated regarding whether being without the NAT1*10 allele could in the future be shown to be a potential marker for the risk of bladder cancer.